2002
DOI: 10.4102/jsava.v73i4.583
|View full text |Cite
|
Sign up to set email alerts
|

Raising livestock in resource-poor communities of the North West Province of South Africa - a participatory rural appraisal study

Abstract: A participatory research model was used in six village communities in the Central Region of the North West Province of South Africa in order to achieve the following broad objectives : to obtain information on the challenges owners face in raising livestock in these areas and to evaluate the livestock owners' level of knowledge of internal parasites in their animals. Information obtained at participatory workshops clearly indicated a need for improvements in water supply, schools, job creation, and health serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…Deworming appears to be a frequent practice, but efficacy may be questionable, as owners deworming their animals were also significantly (P < 0.05) more likely to state that worms were a health problem in their cattle. This fact and that long intervals between worm treatments occurred, support the likelihood of inefficacy of internal parasite treatment, an effect that was also observed by Getchel et al 4 , who also found that the medication is often severely underdosed. To address this, deworming practices and treatments applied should be further investigated and advice on appropriate treatment, as well as management practices should be integrated in the programme of farmer's days and other information pathways.…”
Section: Discussionsupporting
confidence: 73%
“…Deworming appears to be a frequent practice, but efficacy may be questionable, as owners deworming their animals were also significantly (P < 0.05) more likely to state that worms were a health problem in their cattle. This fact and that long intervals between worm treatments occurred, support the likelihood of inefficacy of internal parasite treatment, an effect that was also observed by Getchel et al 4 , who also found that the medication is often severely underdosed. To address this, deworming practices and treatments applied should be further investigated and advice on appropriate treatment, as well as management practices should be integrated in the programme of farmer's days and other information pathways.…”
Section: Discussionsupporting
confidence: 73%
“…Animals in both commercial and communal farm land consume these materials during grazing. According to Getchell [ 37 ], livestock in resource-poor communities in South Africa frequently ingest plastic material in a bid to access food material enclosed in polyethene bags. In other parts of Africa, there have been similar reports of high prevalence of plastic in the stomach of cattle by Mohammed and Fromsa [ 6 ], who found 59.6% prevalence in Ethiopia, and Mushonga et al [ 9 ], who reported 65.0% prevalence in Rwanda.…”
Section: Discussionmentioning
confidence: 99%
“…Demands by funding bodies and the wider research culture for concrete and timely deliverables are important reasons why many studies have a pre-set and often rather narrow focus. In some cases, participatory methodologies are used as a first “scoping” stage, to set more detailed priorities for further research or development activities ( 4 , 34 , 35 ). Other studies focus on singling out “the most important disease in the studied community,” signifying a compartmentalistic view of animal management and health grounded in an illusion of a healthy animal being struck by a solitary disease event ( 36 ).…”
Section: Discussionmentioning
confidence: 99%